2019
DOI: 10.17816/jowd68183-92
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor as a checkpoint of the embryo invasive potential and endometrial receptivity

Abstract: Granulocyte colony-stimulating factor (G-CSF) promotes proliferation, survival, and differentiation of myeloid-lineage cells, as well as normal hematopoietic cells. The immunomodulating effects of G-CSF, which consist in stimulating the Th2 biased type immune response, prevent the development of graft-versus-host disease (GvHD) and, as a special case of GvHD, are responsible for the embryo implantation into the endometrium after the embryo transfer. G-CSF stimulates subpopulations of neutrophils, which display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The results of the present study also agreed with the results published by Tapilskaya et al (2019), which discussed four different meta-analyses exploring the efficacy of administering G-CSF to infertile women undergoing IVF. The authors found increases in implantation and clinical pregnancy rates attributed to changes in endometrial receptivity and/or invasive potential of the developing embryo.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study also agreed with the results published by Tapilskaya et al (2019), which discussed four different meta-analyses exploring the efficacy of administering G-CSF to infertile women undergoing IVF. The authors found increases in implantation and clinical pregnancy rates attributed to changes in endometrial receptivity and/or invasive potential of the developing embryo.…”
Section: Discussionsupporting
confidence: 91%